Magnesium Replacement Improves the Metabolic Profile in Obese and Pre-Diabetic Patients with Mild-to-Moderate Chronic Kidney Disease: A 3-Month, Randomised, Double-Blind, Placebo-Controlled Study - Omer Toprak; Huseyin Kurt; Yasin Sarı; Cihat Şarkış; Halil Us; Ali Kırık (Karger Publishers, 2017)
Background/Aims: Magnesium is an essential mineral for many metabolic functions. There is very little information on the effect of magnesium supplementation on metabolic profiles of chronic kidney disease (CKD) patients. The aim of this study was to assess the influence of magnesium supplementation on metabolic profiles of pre-diabetic, obese and mild-to-moderate CKD patients with hypomagnesemia. Methods: A total of 128 hypomagnesemic, pre-diabetic and obese patients with an estimated glomerular filtration rate between 90 and 30 ml/min/1.73m2 were enrolled in a randomised, double-blind, placebo-controlled trial. Patients in the magnesium group received 365 mg of oral magnesium (n = 57) once daily for 3 months, while patients in the control group received a placebo (n = 61), also once daily for 3 months. Hypomagnesemia is defined by a serum magnesium level <1.8 mg/dl in males and <1.9 mg/dl in females; obesity is defined as a body mass index ≥30 kg/m2; and pre-diabetes is defined as fasting plasma glucose ≥100 but <126 mg/dl. The primary end point of the study was the change in insulin resistance measured by the homeostastic model assessment for insulin resistance (HOMA-IR). Results: At the end of follow-up, insulin resistance (-24.5 vs. -8.2%, P = 0.007), HOMA-IR index (-31.9 vs. -3.3%, P < 0.001), hemoglobin A1c (-6.6 vs. -0.16%, P < 0.001), insulin (-29.6 vs. -2.66%, P < 0.001), waist circumference (-4.8 vs. 0.55%, P < 0.001) and uric acid (-0.8 vs. 2.2%, P = 0.004) were significantly decreased in terms of mean changes; albumin (0.91 vs. -2.91%, P = 0.007) and magnesium (0.21 ± 0.18 vs. -0.04 ± 0.05 mg/dl, P < 0.001) were significantly increased in those taking magnesium compared with a placebo. The decrease in metabolic syndrome (-10.5 vs. -4.9%, P = 0.183), obesity (-15.7 vs. -8.2%, P = 0.131), pre-diabetes (-17.5 vs. -9.8%, P = 0.140), and systolic (-5.0 ± 14.8 vs. 0.22 ± 14.9 mm Hg, P = 0.053) and diastolic (-3.07 ± 9.7 vs. 0.07 ± 9.6 mm Hg, P = 0.071) blood pressure did not achieve to a significant level after study. Conclusion: Our data support the argument that magnesium supplementation improves the metabolic status in hypomagnesemic CKD patients with pre-diabetes and obesity.